Epigenetics: A Modern Science Controlling Gene Expression - qizi, Muroddinova Farida Rakhmatboy (American Journal of Biology and Natural Sciences, 2025)
Epigenetics is a branch of science that studies mechanisms regulating gene expression without altering the sequence of genetic material (DNA). This article highlights the fundamental concepts of epigenetics, molecular mechanisms, its significance in the organism, and its role in medicine, particularly oncology, developmental biology, and hereditary diseases. Furthermore, the influence of environmental factors, nutrition, stress, toxins, and lifestyle on epigenetic changes is analyzed. The importance of epigenetic research in healthcare and preventive medicine is emphasized, along with considerations of future prospects.